Robustness of Catalytically Dead Cas9 Activators in Human Pluripotent and Mesenchymal Stem Cells - Paolo Petazzi; Raul Torres-Ruiz; Antonella Fidanza; Heleia Roca-Ho; Francisco Gutierrez-Agüera; Julio Castaño; Sandra Rodriguez-Perales; Rafael Díaz de la Guardia; Belén López-Millán; Anna Bigas; Lesley M. Forrester; Clara Bueno; et al. (Molecular Therapy: Nucleic Acids, 2020)
Human pluripotent stem cells (hPSCs) and mesenchymal stromal/stem cells (hMSCs) are clinically relevant sources for cellular therapies and for modeling human development and disease. Many stem cell-based applications rely on the ability to activate several endogenous genes simultaneously to modify cell fate. However, genetic intervention of these cells remains challenging. Several catalytically dead Cas9 (dCas9) proteins fused to distinct activation domains can modulate gene expression when directed to their regulatory regions by a specific single-guide RNA (sgRNA). In this study, we have compared the ability of the first-generation dCas9-VP64 activator and the second-generation systems, dCas9-SAM and dCas9-SunTag, to induce gene expression in hPSCs and hMSCs. Several stem cell lines were tested for single and multiplexed gene activation. When the activation of several genes was compared, all three systems induced specific and potent gene expression in both single and multiplexed settings, but the dCas9-SAM and dCas9-SunTag systems resulted in the highest and most consistent level of gene expression. Simultaneous targeting of the same gene with multiple sgRNAs did not result in additive levels of gene expression in hPSCs nor hMSCs. We demonstrate the robustness and specificity of second-generation dCas9 activators as tools to simultaneously activate several endogenous genes in clinically relevant human stem cells.